Profile of the alcohols produced in fermentations with malt contaminated with trichothecenes - Reinehr,Christian Oliveira (2003)
In order to study the influence of mycotoxins on the production of alcohols, a fermentative process on a laboratorial scale was simulated. Malt was contaminated with deoxynivalenol and T-2 in different ratios (up to 500 ppb), according to a 3² factorial design, and the alcohols obtained after the fermentation were determined through gas chromatography. The results showed that trichothecenes influenced the profile of the alcohols produced by Saccharomyces cerevisiae during the fermentative process of malt, especially the profile of methyl and isoamyl alcohols.